MODEL PROFESIONALISME GURU PADA MASA KHALIFAH HARUN AL-RASYID - Muhammad Ilham Akbar (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2019)
Starting from the city of Baghdad the golden age of Islamic civilization was achieved by the Abbasid dynasty which was headed by the Caliph Harun al-Rasyid. The city of a thousand nights was made a source of motivation throughout the world for a transformation of civilization. The various fields were repaired by Harun al-Rasyid starting from administration, governance, and Social-ekonomi. But he was more in science and education. It proved to be the leadership of Harun al-Rasyid giving birth to scholars, and Muslim scholars and development on a number of educational institutions. Harun al-Rasyid as the Caliph intervened in scholarly development affairs, ranging from education curriculum, educational methods, the character of an educator who must conform to the established criteria and welfare of an educator Note. Until an educator at the time of caliphate Aaron Al-Rasheed obtained a glorious place. Writing This article uses the 'library' approach with historical-descriptive methods. Keywords: Islamic civilization, Harun al-Rasyid, Education, Teacher Position